Two new luminescent ternary Cd(II)-MOFs by regulation of aromatic dicarboxylate ligands used as efficient dual-responsive sensors for toxic metal ions in water. (1st February 2019) - Yang, Ying-Jie; Liu, Dong; Li, Yue-Hua; Dong, Gui-Ying
Graphical abstract: Two luminescent Cd(II) metal–organic frameworks (MOFs) based on 1, 4-bis(benzimidazol-1-yl)-2-butene ligand were hydrothermally synthesized for the first time, 1 exhibits a five-fold interpenetratingdia network, while2 displays 2D network withsql topology.1 exhibits highly efficient luminescence response for Cu 2+ and Cr2 O7 2−, while2 displays high luminescence quenching efficiency for Hg 2+ and Cr2 O7 2− . Abstract: Two new Cd(II) metal–organic frameworks (MOFs) formulated as [Cd(L)(atpa)] n (1 ) and [Cd(L)(tbta)(H2 O)] n (2 ) [H2 atpa = 2-aminoterephthalic acid, H2 tbta = tetrabromoterephthalic acid, L = 1, 4-bis(benzimidazol-1-yl)-2-butene] were hydrothermally synthesized.1 –2 were characterized by IR spectroscopy, elemental analysis, and single-crystal X-ray diffraction.1 displays a 3D framework with five-fold interpenetratingdia topology.2 holds a 2D corrugatedsql layer. Both MOFs were confirmed to be dual-responsive luminescent sensors (Cu 2+ and Cr2 O7 2− for1, Hg 2+ and Cr2 O7 2− for2 ) in water through the luminescence quenching experiments. The detection limits for these species were 1.2 μM (Cu 2+ ) and 0.29 μM (Cr2 O7 2− ) of1, 0.043 μM (Hg 2+ ) and 0.13 μM (Cr2 O7 2− ) of2, respectively. The luminescence quenching mechanism was investigated.